Inpatient Satisfaction To Attribute of Health Service Quality Dimensions in Hospitals in Indonesian - Agustini, Sri; Idris, Haerawati; Misnaniarti, Misnaniarti (Jurnal Midpro, 2020)
The hospital is one of the health service facilities that play a very important role in providing health services to the community. To increase patient satisfaction in the hospital, it is necessary to evaluate the quality of existing health services both from a technical and administrative perspective. This study aims to describe inpatient satisfaction with the attributes of the health services quality dimension in hospitals in Indonesia. This study used secondary data with a cross-sectional design based on Risnakes data in 2017. The sample used is samples of Risnakes in hospitals in 2017 after deducting missing data, namely 7,287 inpatients from 380 hospitals in Indonesia. Data analysis used univariate analysis. Results of this study showed that the level of inpatient satisfaction to the attribute of health service quality dimensions in private hospitals was better than in government hospitals. In the tangible dimension of the various attributes studied, there are 5 attributes still below the standard of patient satisfaction (90%), while for the reliability dimension there are 2 attributes, the responsiveness dimension 5 attributes, the assurance dimension 2 attributes, and empathy dimensions 3 attributes. To improve the quality of health services, the management of all hospitals in Indonesia needs to routinely evaluate all of the attributes of health service quality dimensions in the hospital.Â Â